Design of Monitoring and Fire Extinguishing System Based on the Internet of Things in Unmanned Vehicles - Agustin, Sarah; Muhammad Suranegara, Galura; Setyowati, Endah (APIC, 2024)
Currently, people are often unaware of the existence of hotspots or gas leaks in the house which can trigger large fires in the house. Therefore, this research focuses on designing a fire monitoring and extinguishing system that can detect early IoT-based fires using the SIM800L GSM module on unmanned vehicles to detect fires and immediately extinguish them, accompanied by sending emergency messages via the SMS application on smartphones. As a warning, a fire has been detected in the house so that people can be more alert. In addition, this system is designed so that the vehicle can be controlled remotely using the HC-06 Bluetooth module and Bluetooth RC Car. This early fire detection process will be tested 30 times, each sample will be tested for the time speed obtained in detecting and extinguishing a fire. Thus, this system has the potential to prevent fires which can cause major losses.